Streptococcus mutans counts in plaque adjacent to orthodontic brackets bonded with resin-modified glass ionomer cement or resin-based composite - Solange Machado Mota (Brazilian Oral Research, 2008)
This study investigated the number of Streptococcus mutans CFU (colony forming units) in the saliva and plaque adjacent to orthodontic brackets bonded with a glass ionomer cement - GIC (Fuji Ortho) or a resin-based composite - RC (Concise). Twenty male and female patients, aged 12 to 20 years, participated in the study. Saliva was collected before and after placement of appliances. Plaque was collected from areas adjacent to brackets and saliva was again collected on the 15th, 30th, and 45th day after placement. On the 30th day, 0.4% stannous fluoride gel was applied for 4 minutes. No significant modification in the number of Streptococcus mutans CFU in saliva was observed after placement of the fixed orthodontic appliances. On the 15th day, the percentage of Streptococcus mutans CFU in plaque was statistically lower in sites adjacent to GIC-bonded brackets (mean = 0.365) than in those adjacent to RC-bonded brackets (mean = 0.935). No evidence was found of a contribution of GIC to the reduction of CFU in plaque after the 15th day. Topical application of stannous fluoride gel on the 30th day reduced the number of CFU in saliva, but not in plaque. This study suggests that the antimicrobial activity of GIC occurs only in the initial phase and is not responsible for a long-term anticariogenic property.